Fragment on Kropotkin and Giuliani - HARNEY, Stephen Matthias (Institutional Knowledge at Singapore Management University, 2002)
Kropotkin's history of the French Revolution has a revealing chapter on anarchists. 1 Kropotkin notes that they were greatly feared by both the Girondins and the Jacobins, and they dominated many key moments of action and deliberation in the Revolution. Yet they left behind little direct trace, except in the pamphlets of others in which they were attacked. And Kropotkin's great history enacts this presence. Anarchists are given only one short chapter, but they are present as a force in every scene. They were the people willing to make revolution at every turn, "even against themselves." These anarchists were precisely, in Kropotkin's history, both the movement and limits of the French Revolution.